Indefinite causal order in cavity quantum electrodynamics - Castaños-Cervantes, Luis Octavio; Procopio Peña, Lorenzo Manuel; Bartley, Tim J. (Physical Review Research)
Indefinite causal order (ICO) has the potential to be a new resource for quantum information processing. In most of its experiments, ICO has been investigated in a photonic platform. Here, we investigate ICO in a cavity quantum electrodynamics system composed of two cavities. Our results show that ICO can create highly entangled states of two distant cavity fields that never interact directly independent of the initial (excited or ground) state of the atom. These entangled states can have the form of one- or two-photon NOON states. We show that ICO can interchange one photon between both cavities without changing the state of the atom, something that is impossible to achieve for two cavities in well-defined order. Furthermore, the vacuum Rabi oscillations either disappear or lose their sinusoidal form with ICO. Our results show the potential that ICO can offer in the paradigm of light-matter interaction for coherently controlling atom-field observables.

Bildungstechnologie in der schulischen Bildung - Herzig, Bardo (The Age of EdTech: Bildungstechnologie im Spannungsfeld zwischen Innovation und Qualität)

Source Code-Driven GDPR Documentation: Supporting RoPA with Assessor View - Khedkar, Mugdha; Schlichtig, Michael; Bodden, Eric (IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))

The spatial and sectoral incidence of Germany’s COVID-19 insolvency gap - Rahali, Mahdi; Kosi, Urska; Gassen, Joachim

From Avatar Cues to Pseudonymity Modes: Identity Perception in Social Virtual Reality - Tölle, Laura; Rose, Robert; Trier, Matthias

Semi-homogeneous vector bundles on abelian varieties: moduli spaces and their tropicalization - Gross, Andreas; Kaur, Inder; Ulirsch, Martin; Werner, Annette (Moduli)
Abstract Let $A$ be an abelian variety with totally degenerate reduction over a non-Archimedean field. We describe the moduli space of semi-homogeneous vector bundles on $A$ from the perspective of non-Archimedean uniformization and show that the essential skeleton may be identified with a tropical analogue of this moduli space. For $H=0$ our moduli space may be identified with the moduli space $M_{0,r}(A)$ of semi-stable vector bundles with vanishing Chern classes on $A$ . In this case we construct a surjective analytic morphism from the character variety of the analytic fundamental group of $A$ onto $M_{0,r}(A)$ , which naturally tropicalizes. One may view this construction as a non-Archimedean uniformization of $M_{0,r}(A)$ .

Scaling Bottom-Up IFDS Taint Analysis with Optimized Data-Flow Encoding - Schiebel, Fabian Benedikt; Bodden, Eric (40th European Conference on Object-Oriented Programming (ECOOP 2026))

Surface initiated radical-promoted cationic photo-polymerization from silica nanoparticles employing a trisacylgermanium photoinitiator - Zhang, Zizheng; Müller, Matthias W.; Schmallegger, Max; Paris, Matthias; Haas, Michael; Gescheidt, Georg; Gutmann, Torsten; Griesser, Thomas; Kern, Wolfgang; Bandl, Christine (European Polymer Journal)

Static Analysis Traces can Help Dynamic Symbolic Execution: a Replication Study - Kummita, Sriteja; Schiebel, Fabian Benedikt; Bodden, Eric; Miao, Miao; Wei, Shiyi (2026 IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))

Multicomponent Betti reaction affords covalent organic framework nanoreactor for palladium-catalyzed nitroarene reduction - Salarinejad, Neda; Dinari, Mohammad; Lins, Jonas; Gutmann, Torsten; Chae, Keun Hwa (Communications Chemistry)

Modellgestützte Optimierung eines Ultraschall-Torsionsschweißsystems - Dohmen, Markus Daniel; Bornmann, Peter; Littmann, Walter; Hemsel, Tobias; Sextro, Walter (PLUS-Elektronikfertigung)

A comprehensive numerical study of the wetting behavior in structured packings with a direct consideration of the packing microstructure - Dechert, Christopher; Riese, Julia; Kenig, Eugeny (Chemical Engineering Science)

Steuersicherheit als Standortfaktor: Planbarkeit statt Investitionshemmnis - Sureth, Caren (Betriebs-Berater)

Verstehen adressieren und Darstellungen vernetzen: Exemplarische Aufgaben zur analytischen Geometrie - Herrmann, Janine; Hoffmann, Max; Wessel, Lena (Mathematikabitur „Status Quo – Quo Vadis“: Tagungsband zur Fachtagung zum Mathematikabitur am 11./12. Februar 2025 in Dresden)
Keywords: Verstehensorientierung; Darstellungsvernetzung; analytische Geometrie; Abitur; Aufgabenentwicklung; Lehrkräfteprofessionalisierung

Different Pathways, Shared Challenges: Reflections on Entering Vocational Teaching in Germany - Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin
Germany is experiencing a shortage of teachers, a situation that is particularly evident in the domain of technical vocational education. In response to this, various pathways into vocational teacher education have been established. These pathways are diverse in their nature but all lead to the same teacher degree as traditional teacher education. In two interview studies (n=22 (pre service) vocational teachers), initial motives of entering teacher education (based on FIT-Choice) as well as retrospective views on the career choice after entering the profession (based on PLP model) are analyzed. The present study compares the reflective views of pre-service teachers and career-changing in-service teachers (CCIT). Although both groups generally perceive their career choice positively, the results raise questions about why CCITs did not enter the field of teacher education in the first place. Additionally, the analysis allows for further discussion about existing teacher education programs in times of teacher shortage.
Keywords: vocational teacher education; teacher shortage; career-changing teachers; teacher reflections

Zwischen konstitutioneller Dreisprachigkeit und realer Vielsprachigkeit: Die multilinguale Diversität in Luxemburg - Liechty, Vincent
Luxemburg gilt als Musterbeispiel für sprachliche Vielfalt: Die drei Amtssprachen Luxemburgisch, Französisch und Deutsch treffen migrations- und globalisierungsbedingt auf zahlreiche weitere Sprachen wie Portugiesisch und Italienisch. Der Artikel beleuchtet historische Entwicklungen, Sprachenpolitik und Alltagspraxis sowie Chancen wie Herausforderungen der mehrsprachigen Diversität in Luxemburg.

Shifting Minds or Reinforcing Myths? Empirical Insights into AI-related Affective Changes Among Future Technology Teachers - Vernholz, Mats; Schäfers, Johannes; Jonas-Ahrend, Gabriela; Temmen, Katrin

Exploring (De)Motivating Factors over Time: Perspectives of Career Change STEM Teachers from Germany and Israel - Guberman, Ainat; Jonas-Ahrend, Gabriela; Arvif-Elyashiv, Rinat; Ben-Yehduah, Gal; Cyprus, Dominik

The True Story Of A Total Fake. Eine Untersuchung des didaktischen Potenzials der Hochstaplerin Anna Delvey in der Miniserie Inventing Anna - Intveen, Julie (Hochstapelei in der Gegenwartskultur. Literaturwissenschaftliche und literaturdidaktische Perspektiven)
Figuren der Hochstapelei faszinieren als Meister:innen der Verstellung. Ob in Literatur, Film oder Realität – sie inszenieren sich virtuos und entlarven die Oberflächlichkeit einer Gesellschaft, die sich von Äußerlichkeiten blenden lässt. Sie stellen soziale Grenzen infrage und verkörpern einen subversiven Geist, der den Wunsch nach Ausbruch widerspiegelt. Doch was poetisch bewundert wird, ist real oft justiziabel und hat zerstörerische Folgen für die Betrogenen. Dieser Band nähert sich der Hochstapelei als kultureller Praxis der Gegenwart. Welche gesellschaftlichen, kulturellen und medialen Bedingungen begünstigen das Hochstapeln? Und was bedeutet es für die Identitätsarbeit in der Moderne, wenn die Grenzen zwischen Sein und Schein verschwimmen? Anknüpfend an bisherige Forschungsdiskussionen versammeln die literaturwissenschaftlichen und literaturdidaktischen Beiträge Antworten auf diese Fragen. Darüber hinaus beleuchten sie die enge Verknüpfung von Fiktion, Täuschung und Selbstinszenierung.

Praxisforschung in Schule und Unterricht - Textor, Annette; Kullmann, Harry; van der Donk, Cyrilla; van Lanen, Bas
Für Lehrer*innen ist es wichtig, über die Qualität ihrer Arbeit informiert zu sein, um sich an Schul- und Unterrichtsentwicklung beteiligen zu können. Das vorliegende Lehrbuch bietet anhand eines erprobten Modells – eines Forschungszyklus in Verbindung mit einem ergänzenden Innovationszyklus – konkrete Hilfestellungen, um die eigene Tätigkeit zu reflektieren und weiterzuentwickeln. Der zugrundeliegende Ansatz verbindet erfolgreiche Verfahren aus der niederländischen Lehrerinnen- und Lehrerbildung mit etablierten Methoden der schulischen Praxisforschung im deutschsprachigen Raum. Zahlreiche alltagsbezogene Beispiele illustrieren die Grundsätze und Verfahrensschritte, während Übungsaufgaben zu Vertiefung und Wiederholung anregen.
Keywords: Praxisforschung; Schulentwicklung; Inklusion; Data Literacy